Development and Implementation of a Global Health Elective with a Drug Discovery Game for Pharmacy Students - Jordan R. Covvey; Anthony J. Guarascio; Lauren A. O'Donnell; Kevin J. Tidgewell (MDPI AG, 2017)
Interest in global health education within the pharmacy curriculum has increased significantly in recent years. However, discussion of different models and methods to evaluate course structures are limited. The overall objective was to (1) describe the structure of our global health elective for pharmacy students, and (2) assess educational outcomes related to perceived/formal knowledge and attitudes associated with global health. Our elective was designed using a competency-centered approach to global health education, incorporating reflection, projects, service and game-learning. In addition to course assessments, a pre-post survey questionnaire assessing attitudes, knowledge perception, formalized knowledge and opinions was utilized. Overall, students demonstrated appropriate performance on course assessments, temporally improving throughout longitudinal projects. The survey demonstrated significant increases in knowledge perception as a result of the course; however, no change in formalized knowledge was evident through the survey assessment. Additionally, the incorporation of game-learning into the course was well received by students. Future iterations of the course will focus on utilization of different assessment methods to meet learning outcomes.